TINGKAT PEMANFAATAN FASILITAS SARANA DAN PRASARANA REKREASI PANTAI KELURAHAN MATRAS SUNGAILIAT BANGKA - Denik Mardiatin; Wahyu Adi; Kurniawan Kurniawan (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Kelurahan Matras is one of the places contained that have a high enough tourism potential. This study aims to determine the level of utulization of facilities and infrastructure as well as analyzing development strategis. Yhis research was conducted in December 2016 using side purposive method and analysis. The result obtained are the highest utilization rate is the beach Matras and Beach Parai Tenggiri with very good criteria (80-100%), as wel as development strategis needs to do is increase the amount of facilities and infrastructure needed, in order to increase revenue to be the object sustainable tourism.